2021
DOI: 10.3390/life11040269
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Potential Targets for Cell-Based Therapies on Melanoma Cells

Abstract: Tumor antigen-specific redirection of cytotoxic T cells (CTLs) or natural killer (NK) cells including chimeric antigen receptor (CAR-) and T cell receptor (TCR-) cell therapy is currently being evaluated in different tumor entities including melanoma. Expression of melanoma-specific antigen recognized by the respective CAR or TCR directly or presented by HLA molecules is an indispensable prerequisite for this innovative therapy. In this study, we investigated in 168 FFPE tumor specimens of patients with stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Strobel S.B. et al observed HER2 overexpression in 3% of human primary melanomas [ 52 ]. However, all of the melanoma cell lines they tested uniformly expressed HER2.…”
Section: Discussionmentioning
confidence: 99%
“…Strobel S.B. et al observed HER2 overexpression in 3% of human primary melanomas [ 52 ]. However, all of the melanoma cell lines they tested uniformly expressed HER2.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-melanosome protein (PMEL; PMEL17; glycoprotein 100, gp100) ordinarily plays a role in melanin synthesis and is highly specific to melanoma [181]. Because PMEL is broadly overexpressed (61-90%) in melanoma patients [175,181,182], independent of their stage of disease progression, PMEL is of especially great interest as a therapeutic target. CAR-NK92MI cells bearing TCR-like CARs were assembled by selecting the TCR-like antibody GPA7 against the PMEL/HLA-A2 complex and then fused to the intracellular domain of a CD3-ζ chain [175].…”
Section: Pre-clinical Car-nk Studies With Meaningful Implications For...mentioning
confidence: 99%
“…Marx et al discovered that there was lower expression in the core of glioblastoma multiforme than in the margin of the tumor ( Marx et al, 2020 ). Melanomas express a large amount of GD2 that is widely distributed on the membrane of tumor cells and in the cytoplasm ( Strobel et al, 2021 ). Hersey et al detected that the expression of disialogangliosides GD2 was higher in metastatic melanomas than in primary melanomas, which revealed that the expression of GD2 was probably associated with the metastatic potential of the tumor ( Hersey et al, 1988 ).…”
Section: Gangliosidesmentioning
confidence: 99%